Membrane of chitosan with essential oils of Romero and Tree of Tea: Potential as biomaterial - Quihui Cota, L.; Morales Figueroa, G. G.; Valbuena Gregorio, E.; Campos García, J. C.; Silva Beltrán, N. P.; López Mata, M. A. (Revista Mexicana de Ingenieria Biomedica, 2017)
Chitosan (CH) has hemostatic properties and accelerated healing ability to stimulate the host immune system against viral and bacterial infections. It is also biodegradable, nontoxic, antimicrobial, biocompatible, and capable of forming membranes and to carry and to release bioactive compounds. These properties of CH can be useful to carry some volatile essential oils having bioactive compounds (antioxidants and antimicrobials) with potential application in human health as those as rosemary (RMO) [Rosmarinus officinalis] and tea tree (TTO) [Melaleuca alternifolia]. These essential oils were incorporated into the chitosan by the casting method in this study. The physical properties (solubility, PVA, transparency and blocking ultraviolet light) of these membranes with TTO and RMO (0.25, 0.50 and 1.00% v/v), antioxidant capacity and protection human erythrocyte were evaluated. TTO and RMO reduced solubility (28-58%) and PVA (between 28-58%) of CH membranes. All membranes were yellow, slightly opaque and they were able to block the ultraviolet light. Membranes also showed relatively low antioxidant capacity by the radical ABTS (≈ 6 at 9%), but it was accompanied by an excellent protective effect on the human erythrocyte (> 63%).